From hegemony crisis to the rise of Asia – Pacific region. China in current world geopolitic scene (Huellas, 2021)
The main purpose of this article is to analyze the USA hegemony crisis and the economic rise experienced by the Asia-Pacific region. Global power is located in new territories, shifting from the North-West axis to the South-East axis. According to Giovanni Arrighi (2007), the hegemonic cycle of the United States is in its declining phase, consequently without being able to impose its world geopolitical order no longer. The rise of Southeast Asia experienced in the 1990s resulted in a shift of power to this region. In particular, China appears as the main competitor of the United States, especially in key high-tech nodes. The insubordination of the Asian giant allowed for a fabulous economic rise, companies greater competitiveness in comparison to those of American capital and a displacement of geopolitical power. China replaces Japan as the regional leader, in addition to becoming the main trading partner for Africa and Latin America. The trade war between the United States and China reveal the terminal crisis of hegemony. Consensus no longer exists, but domination without hegemony. The door is open for a new hegemonic cycle, will it be Chinese?
Keywords: Hegemony; China; United States; Geopolitics; Global power